A three-dimensional model simulation of the impact of Mt. Pinatubo aerosol on the Antarctic ozone hole - Knight, JR; Austin, J; Grainger, R; Lambert, A (1998)
Seasonal integrations of a three-dimensional fully coupled model of the radiation, dynamics and chemistry of the stratosphere and mesosphere are presented for the southern hemisphere spring. Included in the model are heterogeneous reactions which take place in sulphuric acid aerosol droplets as well as on the surface of Polar Stratospheric Clouds (PSCs). Calculations are performed for background levels of stratospheric aerosol and for conditions following the eruption of Mt. Pinatubo. For the volcanic case, surface area densities are derived from Improved Stratospheric and Mesospheric Sounder data. For background aerosol loadings there are significant increases in HOx and ClOx, as well as reductions in NOx. These effects are enhanced following the Pinatubo eruption but saturate at relatively low aerosol levels and hence can persist in the stratosphere for several years. Where pSCs are predicted to form, the sulphate aerosol chemistry does not operate in the model since the aerosols are incorporated as nuclei within the PSCs. In contrast, on the edge of the ozone hole, where temperatures are only just too high for the formation of PSCs, destruction by aerosol can result in further total ozone depletion of order 20 Dobson Units. In addition, the size and duration of the ozone hole are both increased by the presence of volcanic aerosols. The results support previous suggestions that the eruption of Mt. Pinatubo resulted in a temporary increase in ozone depletion over Antarctica and elsewhere.